Sovereignty and the Sacred: Secularism and the Political Economy of Religion, written by Robert A. Yelle - Koch, Anne (Journal of religion in Europe, 2019)
"Sovereignty and the Sacred: Secularism and the Political Economy of Religion, written by Robert A. Yelle" published on 24 Jan 2019 by Brill.